2017
DOI: 10.1590/s0100-204x2017001100020
|View full text |Cite
|
Sign up to set email alerts
|

Temperature changes in soil covered by black oat straw

Abstract: -The objective of this work was to evaluate the effect of different amounts of black oat (Avena strigosa) straw covering soil surface on soil temperature at different depths. The treatments consisted of 0, 3, 6, and 9 Mg ha -1 straw. Soil temperature was measured hourly by a thermocouple inserted at different depths (0, 5, 15, 30, and 50 cm) and was used to adjust an equation correlating the temperature of covered soil with that of bare soil. With the correlations, it was possible to observe a point value of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(16 reference statements)
0
1
0
1
Order By: Relevance
“…Durante los primeros 46 DDS y en el período de los 67-81 DDS, las plantas crecidas bajo el sistema de LM (128 kg N ha -1 ), reflejaron un mayor número de hojas que las plantas cultivadas bajo LC. Este hecho se explicaría debido a que, durante los primeros días de establecimiento del cultivo, la labranza del suelo incrementa su temperatura y promueve un mayor desarrollo radicular que suelos no trabajados (Varsa et al, 1997;Zwirtes et al, 2017). Sin embargo, al trascurso del tiempo, la aparición de hojas en las plantas resultó igual entre tratamientos y no afectó el rendimiento.…”
Section: Discussionunclassified
“…Durante los primeros 46 DDS y en el período de los 67-81 DDS, las plantas crecidas bajo el sistema de LM (128 kg N ha -1 ), reflejaron un mayor número de hojas que las plantas cultivadas bajo LC. Este hecho se explicaría debido a que, durante los primeros días de establecimiento del cultivo, la labranza del suelo incrementa su temperatura y promueve un mayor desarrollo radicular que suelos no trabajados (Varsa et al, 1997;Zwirtes et al, 2017). Sin embargo, al trascurso del tiempo, la aparición de hojas en las plantas resultó igual entre tratamientos y no afectó el rendimiento.…”
Section: Discussionunclassified
“…Maintenance of crop residues on the soil surface has been reported as an important management practice that reduces the soil temperature (Zwirtes et al, 2017) and thermal amplitude (Coelho et al, 2013), which in turn, contribute to reducing water losses by evaporation. In this study, significant effects of the straw managements on the soil temperature were observed, mainly in the near-surface soil layer.…”
Section: Effects Of Sugarcane Straw Removal On Soil Temperaturementioning
confidence: 99%